Delayed gastropleural fistula: a rare cause of a persistent pleural effusion after blunt force trauma. Issue 4 (20th April 2021) - Chan, Kin Yik; Keogh, Shane; Aucharaz, Nitin; Temperley, Hugo; O'Driscoll, James; Ravi, Narayanasamy; Tormey, Shona
Abstract: A gastropleural fistula (GPF) is a rare pathological connection between the stomach and pleural cavity. Diagnosis and treatment are frequently delayed due to the lack of specific clinical, laboratory and radiological findings. We describe a case of a 53-year-old gentleman who presented to our institution with respiratory sepsis and a massive haemopneumothorax on imaging. Uniquely, he was discharged a week prior after a splenectomy for a traumatic fall. Gut flora in the pleural fluid and a subsequent positive dye test suggested an aero-digestive connection. Repeat imaging revealed a fistula between stomach and the left pleural cavity through a ruptured diaphragm. He underwent an open sleeve gastrectomy and primary repair of the diaphragm. This is the first GPF in literature presenting in such a fashion. Although rare, a persistent effusion with a history of blunt thoracoabdominal trauma may herald a GPF, which, if not diagnosed promptly, may result in significant morbidity.